Contributos dos webfólios para a formação inicial de professores de Biologia e Geologia - M. Santos (2010)
This work shows an experience that began in September 2009 under Supervised Teaching Practice (PES) and aims the creation of a reflective portfolio foreseen in the IPP regulation. With the construction of this portfolio is intended to go beyond the PES student's evaluation and reflect on how this instrument contributes to the personal and professional development of the stakeholders (trainees and trainers) in the training process